Twin-screw granulation - a systematic analysis of process parameters - Margarethe Richter (University of Huddersfield Press, 2018)
Twin-screw granulation has a significant advantage over traditional granulation methods leading to the possibility of continuous manufacturing. Although this technology has drawn attention in recent years, the general understanding of the process is limited. This study gives a brief overview of the most important process parameters and their influence on product quality. Experimental results from a benchtop granulator and an in-line particle size measurement have been analysed. From this basic study conclusions can be drawn how to tailor the particle size distribution in twin-screw granulation. The most crucial parameters are the liquid-to-solid ratio and the filling level of the screws.